Spanish Language for Tourists: Language Training of Adult Learners in the Context of Intensification - Svetlana V. Shustova; Mariya A. Khrustaleva; Ekaterina A. Beloborodova; María Dolores Mondéjar Fuster (National Research Mordova State University, 2019)
Introduction. Analysis of existing traditional and intensive teaching methods as well as study of ways of its intensification allow the authors to define and integrate most effective methods corresponding to educational needs of a modern person. The article aims to present a model of teaching which allows for realizing a short-term language training of adults for a trip to Spanish- speaking countries. Materials and Methods. The methods of intensification for foreign language teaching targeted at adult learners with due account for their psychological peculiarities were used as material for the article. The creation of stressful situations in the Spanish language class allowed for definition of factors which encourage a more intensive acquisition of linguistic competence. The methods include psycho-andragogical diagnosis (a questionnaire survey for adult learners), experimental learning (the creation of a stressful situation in the class), the observation method (monitoring of psychological and emotional state of adults and the correction of applied stressors), statistical processing of experimental data and its interpretation. Results. The manual "Español para los turistas", developed by the authors, was used in the teaching of the Spanish language in the context of simulated stressful situations which triggered an increase in the motivational capacity of adult learners. Stimulation of stressful situations during the process of acquisition of linguistic competence by adult learners has become an integral tool in learning intensification. Discussion and Conclusion. Use of the created method in the teaching of the Spanish language, in the context of the tourist, allows one to meet existing requirements to modern student for quick and effective language training for tourism abroad. The offered model of intensification can be used in the life-long learning, notably for the training of adults in intercultural communication.